1) Given differential equation is "y^4 \u2212 81y = 0 : y(0) = 20, y'(0) = 39, y''(0) = 108, y'''(0) =1 89" .
Taking Laplace Transform, we get
"L(y^4-81y ) = 0"
Now using Linear property of Laplace, we get
"L(y^4) - 81 L(y) = 0" .
"\\implies (s^4 Y-s^3y(0)-s^2y'(0)-sy''(0)-y'''(0)) - 81 Y = 0" where "L(y(t)) = Y(s)" .
"\\implies (s^4 Y-20s^3-39s^2-108s-189) - 81 Y = 0"
"\\implies (s^4-81)Y = 20s^3+39s^2+108s+189"
"\\implies Y = \\frac{20s^3+39s^2+108s+189}{s^4-81}" .
Now, taking Laplace Inverse transformation on both sides, we get
"y = L^{-1} (\\frac{20s^3+39s^2+108s+189}{s^4-81})"
"=L^{-1}\\left\\{\\frac{4s+9}{s^2+9}+\\frac{3}{s+3}+\\frac{13}{s-3}\\right\\} \\\\\n=L^{-1}\\left\\{\\frac{4s}{s^2+9}+\\frac{9}{s^2+9}+\\frac{3}{s+3}+\\frac{13}{s-3}\\right\\} \\\\\n=4L^{-1}\\left\\{\\frac{s}{s^2+9}\\right\\}+9L^{-1}\\left\\{\\frac{1}{s^2+9}\\right\\}+3L^{-1}\\left\\{\\frac{1}{s+3}\\right\\}+13L^{-1}\\left\\{\\frac{1}{s-3}\\right\\} \\\\\n=4\\cos \\left(3t\\right)+9\\cdot \\frac{1}{3}\\sin \\left(3t\\right)+3e^{-3t}+13e^{3t}"
So, "y =4\\cos \\left(3t\\right)+3\\sin \\left(3t\\right)+3e^{-3t}+13e^{3t}" .
2) "L \\{f(t)H(t\u2212 a)\\}=e^{\u2212as}L \\{f(t+ a)\\}"
Hence, "L\\{ (t^2-8t+9 ) H(t-4) \\} = e^{-4s} L\\{ (t+4)^2-8(t+2)+9 \\}"
"= e^{-4s} L\\{ t^2 +9 \\} = e^{-4s} (\\frac{2}{s^3}+\\frac{9}{s})" .
Comments
Leave a comment